(untitled) (Universal International Scientific Journal, 2026)
This article examines the theoretical and applied aspects of the relationship between academic procrastination and metacognitive processes. The aim of the study is to identify the relationship between the level of metacognitive processes in students and the severity of academic procrastination, as well as to analyze the ethnocultural characteristics of this phenomenon. Modern scientific approaches to understanding the nature of academic procrastination, its psychological determinants, and the role of metacognitive processes in learning are presented. The results indicate that a low level of metacognitive regulation is associated with a greater tendency toward procrastination.